Cavitation in strained polyethylene/aluminium oxide nanocomposites. (February 2017) - Liu, D.; Pallon, L.K.H.; Pourrahimi, A.M.; Zhang, P.; Diaz, A.; Holler, M.; Schneider, K.; Olsson, R.T.; Hedenqvist, M.S.; Yu, S.; Gedde, U.W.
Graphical abstract: Highlights: Kinetics of cavitation during straining of nanocomposites were assessed by scanning electron microscopy. Microstructural changes at polymer/nanoparticle interface during cavitation was studied by small-angle X-ray scattering coupled with tensile test. Microstructure of nanocomposites at an early stage of cavitation was assessed by X-ray ptychographic computed tomography in 3D. Abstract: The incorporation of metal oxide (e.g. Al2 O3 ) nanoparticles has a pronounced positive effect on low-density polyethylene (LDPE) as an insulating material for high-voltage direct-current (HVDC) cables, the electrical conductivity being decreased by one to two orders of magnitude and charge species being trapped by the nanoparticles. The risk of debonding between the nanoparticles and the polymer matrix leading to electrical treeing via electrical discharges in the formed cavities was the motivation for this study. Scanning electron microscope (SEM), small-angle X-ray scattering (SAXS) and X-ray ptychographic tomography were used to study a series of LDPE nanocomposites which contained Al2 O3 nanoparticles treated with silanes having terminal alkyl groups of different lengths (methyl, octyl and octadecyl). When specimens were subjected to a tensile strain (a typical specimen stretched beyond the onset of necking consisted of three zones according to SEM of specimens that were studied after removal of the external force: an essentially cavitation-free zone with low local plastic strain, a transitional zone in which local plastic strain showed a marked increase and the revealed concentration of permanent cavities increased with increasing plastic strain and a highly strained zone with extensive cavitation), the cavitation occurred mainly at the polymer-nanoparticle interface according to SEM and X-ray ptychographic tomography and according to SEM progressed with increasing plastic strain through an initial phase with no detectable formation of permanent cavities to a period of very fast cavitation and finally almost an order of magnitude slower cavitation. The polymer/nanoparticle interface was fractal before deformation, as revealed by the profile of the Porod region in SAXS, presumably due to the existence of bound polymers at the nanoparticle surface. A pronounced decrease in the interface fractal dimension was observed when the strain exceeded a critical value; a phenomenon attributed to the stress-induced de-bonding of nanoparticles. The strain-dependence of the interface fractal dimension value at low strain levels between composites containing differently treated nanoparticles seems to be an indicator of the strength of the nanoparticle-polymer interface.